Natural and Anthropogenic Sediment Mixing Processes in the South-Western Baltic Sea - Bunke, Dennis; Leipe, Thomas; Moros, Matthias; Morys, Claudia; Tauber, Franz; Virtasalo, Joonas J.; Forster, Stefan; Arz, Helge W. (Frontiers in Marine Science, 2019)
Natural and anthropogenic sediment mixing can significantly impact the fidelity of sedimentary records of climate and environmental variability and human impact. This can lead to incorrect interpretations of the previous state(s) of a given ecosystem, its forcing mechanisms, and its future development. Here, natural and anthropogenic sediment mixing processes (i.e. bioturbation, hydroturbation and direct anthropogenic impact) are investigated in the south-western Baltic Sea by sedimentological, ichnological, geochemical, and radionuclide analyses to assess their impact on time-marker profiles and sediment deposition. Depth profiles of mercury and caesium-137 display a varyingly strong disturbance down to 5-25 cm. The deviations from undisturbed profiles can be used to estimate the relative degree of sediment mixing. Sedimentary fabric analysis of high-resolution X-radiographs provides further insight into bioturbation. Ichnofossils identified in short sediment cores suggest that the primary sedimentary structure is partly overprinted by burrowing organisms living in the upper 5-7 cm of sediment. Meteorological and hydrological data from automated measuring stations combined with results from resuspension experiments show that hydrodynamic events, such as storms and saline water inflows from the North Sea, have the potential to resuspend and laterally transport sediment particles in the south-western Baltic Sea. Partially graded layers in the scale of mm to cm in the investigated cores are likely associated with such hydrodynamic events. Multiple generations of linear traces on the seafloor are made visible through sidescan-sonar mapping and document a strong anthroturbation in the muddy sediments of the Mecklenburg Bight and the Arkona Basin, e.g. by bottom trawling. Depending on the core location and assumed mixing depth, determined mean net linear sedimentation rates range between 0 and 3.5 mm/a and reconstructed net mass accumulation rates range between 0 and 1.86 kg/m2/a in the mud basins. The calculable inventory of anthropogenic contaminants in the sediments illustrates the important, at least temporary storage function of the mud basins and of the adjacent sandy areas over industrial times. The findings of this study help identify the influence of natural and anthropogenic mixing on sediment profiles, and demonstrates the use of mixed sediment profiles for inferring information about past environmental conditions and anthropogenic impact.